KEKUATAN PEMBUKTIAN AKTA BAWAH TANGAN YANG DITOLAK OLEH TERGUGAT DALAM PEMERIKSAAN PERKARA PERDATA - Tasya Sahita; Harjono Harjono (Verstek, 2023)
This research aims to analyze and find out the strength of evidence of private deed evidence which was rejected by other parties or in this case the Defendant and the Judge's considerations in deciding cases and assessing the evidence of private deed in the South Jakarta District Court Verdict Number 54/Pdt.G/2016/Pn. Jkt. Sel. This research is a normative or doctrinal legal research with the nature of prescriptive and applied research. The approach used in this study is a case study approach with primary legal materials and secondary legal materials. The legal material collection technique used is library research. The legal material analysis technique used is the syllogistic method with a deductive mindset, which is based on the major premise and minor premise, which then draw conclusions. Based on this research, it was found that private deed which was rejected by the Defendant has decreased the strength of proof and the burden of proof is free depending on how the judge evaluates in the trial. The Judge's considerations in assessing the evidence of private deed in Verdict Number 54/Pdt.G/2016/Pn.Jkt. Sel have not met the principles of legal certainty, a sense of justice and benefits for the parties.Keywords: Proof, Private Deed, Verdict